Targeted Treatment of Differentiated and Medullary Thyroid Cancer. (2nd August 2011) - Bales, Shannon R.; Chopra, Inder J.
Abstract : The incidence of thyroid cancer is increasing, with a concomitant increase in the number of patients with advanced and metastatic disease. Discoveries regarding the pathogenesis of thyroid cancer have led to the recent development of new therapeutic agents that are beginning to appear on the market. Many of these new agents are targeted kinase inhibitors primarily affecting oncogenic kinases (BRAF V600E, RET/PTC) or signaling kinases (VEGFR, PDGFR). Some of these agents report significant partial response rates, while others attain stabilization of disease as their best response. Their impact on survival is unclear. While these agents target similar pathways, a wide variety of differences exist regarding efficacy and side effect profile. Current expert opinion advises that these agents be used only in a specific subset of patients.